2006
DOI: 10.1590/s0102-86502006000800006
|View full text |Cite
|
Sign up to set email alerts
|

Análise da cicatrização do cólon com uso do extrato aquoso da Orbignya phalerata (Babaçu) em ratos

Abstract: RESUMO Introdução:A cicatrização é processo complexo, com diferentes fases. Embora exista grande variedade de plantas medicinais poucas têm sido investigadas com intenção de melhorar a cicatrização de órgãos e tecidos, dentre elas, a Orbignya phalerata (Babaçu). Objetivo: Analisar comparativamente as alterações tensiométricas e histológicas na cicatrização de anastomoses colônicas proporcionadas pelo uso do extrato aquoso do mesocarpo do Babaçu (Orbignya phalerata). Metodos: Utilizaramse 40 ratos Wistar, macho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
4
0
4
Order By: Relevance
“…Regarding the animals of the babassu group, there were no signs of infection or abscesses in any of them, as well as absence of fistulas, dehiscence or hematoma, a result better than that observed for Baldez, who found a mild surgical site infection and superficial skin dehiscence 9 .…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Regarding the animals of the babassu group, there were no signs of infection or abscesses in any of them, as well as absence of fistulas, dehiscence or hematoma, a result better than that observed for Baldez, who found a mild surgical site infection and superficial skin dehiscence 9 .…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 56%
“…Mononuclear, representing chronic inflammation, were more pronounced on the 7 th day, both in the babassu and andiroba groups, revealing a possible effect of the aqueous extract of babassu. Baldez, when studying the action of the aqueous extract of babassu in colon healing in rats, showed similar results 9 .…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Previous studies have demonstrated that the babassu mesocarp has been traditionally used to treat inflammatory diseases (Agra et al, 2007), and the native communities have reported the use of babassu mesocarp to treat gastritis, leukorrhea and rounds . The biological effects of babassu mesocarp have been reported, including antiinflammatory effects (Silva and Parente, 2001;Baldez, 2006;Nascimento et al, 2010;Silva et al, 2015). However, previous studies have shown that aqueous babassu mesocarp extract induces both in vitro and in vivo nitric oxide (NO) and tumor necrosis factor α (TNF-α) production in peritoneal macrophages (Nascimento et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…O mesocarpo transformado em pó é peneirado, umedecido e finalmente torrado em fogo alto. O interesse na farinha de mesocarpo de babaçu está pautado nas suas propriedades medicinais, tais como anti-inflamatória alterações nas funções gastrointestinais, redução nos níveis de colesterol, glicemia e insulina pós-prandial (Baldez et al, 2006). Contudo, mesmo apresentando excelentes propriedades há uma deficiência de estudos que tratem desse subproduto do babaçu.…”
Section: Introductionunclassified